기존의 치료에 반응하지 않는 다발성 간전이 대장암 환자에서 방사선조사와 병합한 수지상세포 면역치료의 1, 2상 임상시험 - 최영민(Youngmin Choi), 이형식(Hyung-Sik Lee), 권혁찬(Hyuk-Chan Kwon), 한상영(Sang-Young Han), 최종철(Jong-Cheol Choi), 정주섭(Ju-Seop Chung), 김창원(Chang-Won Kim), 김동원(Dong-Won Kim), 강치덕(Chi-Duk Kang) (Radiation oncology journal, 2008)
목 적: 기존치료에 반응하지 않는 다발성 간전이를 동반한 대장암 환자에서 방사선치료와 병합한 수지상세포 면역 치료의 독성과 반응도를 조사하였다. 대상 및 방법: 2004년 5월부터 2006년 11월까지 다발성 간전이가 동반된 대장암 환자들 중에서 항암화학 요법에 반응하지 않은 환자 중 지원자를 대상으로 연구를 시행하였다. 본 임상 시험에 대하여 동아대학교병원과 부산대학 교병원의 임상윤리심의위원회의 허가를 획득하였고, 동의서에 서명한 환자들을 임상 시험의 대상으로 등록하였 다. 환자의 말초 혈액으로부터 수지상세포를 추출하여 배양하였다. 임상시험 일자에 맞추어서 6×106개의 수지상 세포를 바이알(0.5 ml)에 넣어서 디씨백/아이알 주사를 만들었다. 수지상세포 면역치료는 2주 간격으로 간전이암 조직에 3회 주사하고, 5주에 내약성 평가를 하였다. 내약성 평가를 통과한 환자에게는 8주에 4번째 수지상세포 면 역치료를 하였다. 병의 악화가 없거나 임상시험에 대한 환자의 동의 철회가 없는 경우에는 5, 6번째 수지상세포 면역치료를 각각 12, 16주에 시행하였다. 방사선치료는 수지상세포 면역치료를 주사할 간전이암 부위에 주사하기 전일 및 당일에 4 Gy씩을 조사하였다. 내약성 평가는 3×106개의 수지상세포로부터 시작하여, 12×106개의 수지상 세포까지 시행하였다. 내약성 평가의 최대 내성 용량으로 추가 임상시험을 하였다. 수지상세포 면역치료 주사를 맞은 모든 환자들에서 안전성 평가를 하였다. 4회 이상 주사를 맞은 환자들을 대상으로 10주에 치료 반응을 평가 하여 유효성을 조사하였다. 결 과: 임상시험에 등록한 24명 중 22명에서 수지상세포 면역치료를 시행하였다. 내성약 평가에는 14명이 등록하 여 11명에서 평가를 완료하였다. 시험약과의 관련성이 있을 것으로 생각되는 grade 3 이상의 약물반응으로 인한 이상반응은 없었다. 12×106개의 수지상세포를 내성용량으로 확인하였고, 내성용량인 12×106개 수지상세포 면역 치료를 이용하여 8명에서 추가로 시험을 하였다. 치료에 대한 환자들의 내성은 양호하였고, grade 3을 초과하는 치명적인 부작용은 발생되지 않았다. 4회 이상의 수지상세포 면역치료 주사를 받은 환자가 17명이었고, 이 중의 15명에서는 종양의 반응도 평가가 이루어졌다. 본 연구의 목적은 안전성 평가이지만, 면역치료의 유효성 평가를 위해, 방사선치료와 수지상세포 면역치료 주사가 시행된 부위 외의 간전이암에서 반응도를 조사 하였다. 면역치료 의 반응은 평가가 이루어진 환자들에서 정지성 병변이 4명, 진행성 병변이 11명 이었다. 결 론: 수지상세포 면역치료와 병행한 방사선치료는 이론적으로 국소 및 전신 제어에 상승효과가 있을 것으로 기 대할 수 있다. 하지만 기존 치료에 반응하지 않는 매우 진행된 직장암 환자들을 대상으로 한 본 연구에서는 방사선 치료와 병합한 수지상세포 면역치료로 인한 심각한 부작용의 발생은 없었다는 결과와 4예에서의 정지성 병변의 관찰을 보고한다. 수지상세포의 최대 투여 용량, 적절한 투여 방법, 적절한 방사선의 양, 방사선과 수지상 세포의 적절한 투여 간격 등에 관한 추가 연구를 통하여, 향후 제 2상, 3상 시험으로서의 진행 여부에 긍정적인 결과를 얻을 수 있다고 판단한다. Purpose: To assess the toxicity and tumor response induced by DCVac/IRⓇ dendritic cell (DC) immunotherapy combined with irradiation for refractory colorectal cancer patients with multiple liver metastases. Materials and Methods: Between May 2004 and November 2006, applicants from a pool of refractory colorectal cancer patients with multiple liver metastases were enrolled. The patients were registered after having signed the informed consent form, which had been approved by the Institutional Review Board from the Dong-A University and Busan National University Hospital. DCs were obtained from peripheral blood of each patient, and then cultured in vitro. A total of 6×106 DCs were packed into a vial (DCVac/IRⓇ, 0.5 ml) at the convenience of each patient’s schedule. On the day before and on the day of each vaccination, each patient received a 4 Gy radiation dose to the target tumor. On the day of vaccination, the indicated dose of autologous DCs was injected into the irradiated tumor using ultrasound-guided needle injection procedures. A total of four vaccinations were scheduled at three 2-week intervals and one 4 week interval at the Dong-A University and Busan National University Hospital. If the tumor status was deemed to be stable or responding to therapy, an additional vaccination dose or two was approved at 4 week intervals beyond the fourth immunization. A tolerance test for DCs was conducted by injecting a range of doses (3×106 to 12×106 DCs) after the 3rd injection. Moreover, the maximal tolerable dose was applied to additional patients. Treatment safety was evaluated in all patients who had at least one injection. Treatment feasibility was evaluated by the 10th week by assessing the response of patients having at least 4 injections. For systemic toxicities, the evaluation was performed using the National Cancer Institute Common Toxicity Criteria, whereas adverse effects were recorded using common WHO toxicity criteria. Results: Of the 24 registered patients, 22 received the DCs injections. Moreover, of the 14 patients that applied for the tolerance test, only 11 patients completed it because 3 patients withdrew their testing agreement. A grade 3 or more side effect, which was possibly related to the DC injection, did not occur in additional patients. The 12×106 DC injection was identified as the maximum tolerable dose, and was then injected in an additional 8 patients. Patients tolerated the injection fairly well, with no fatal side effects. In order to assess the feasibility of DC immunotherapy, the response was evaluated in other hepatic lesions outside of the targeted hepatic lesion. The response evaluation was performed in 15 of the 17 patients who received at least 4 injections. Stable and progressive disease was found in 4 and 11 patients, respectively. Conclusion: The DC-based immunotherapy and radiotherapy is theoretically synergistic for the local control and systemic control. The DCVac/IRⓇ immunotherapy combined with irradiation was tolerable and safe in the evaluated cases of refractory colorectal cancer with multiple liver metastases. Future work should include well designed a phase II clinical trials. KCI Citation Count: 0